Wear behavior of boron-doped Ni3Al material at elevated temperature - Solmaz, Y; Kelestemur, MH (Elsevier Science Sa, 2004)
The wear behavior of boron-doped Ni3Al intermetallic compound was investigated at ambient and elevated temperatures. The Ni3Al + B wear samples were prepared by cutting from a 1-mm thick rolled sheet material. Wear tests were carried out on a general purpose wear 1 testing machine having a heating unit and block-disc sample configuration. The counterface material was prepared from 100Cr6 steel. The tests were carried out at temperatures of 25, 100, 300 and 450degreesC. The effects of load and temperatures on the weight loss of Ni3Al + B were determined by using some characterization methods such as scanning electron microscopy (SEM), energy dispersive spectroscopy (EDS) and XRD analysis. The variations of weight loss versus test temperature show a slight decrease in the weight loss except in the case of 50 and 75 N loadings and temperature of 100degreesC. The weight loss values of the tests at the room temperature increase with load. At 100degreesC, the weight losses were about 10-15 times higher than weight loss values in the experiments done at RT. Further, the weight losses reached to the maximum level at 100degreesC compared to the tests done at the higher temperatures 300 and 450degreesC. The results were similar to each other and lower than those done at other temperatures. The changes on the microhardness and friction coefficient versus test temperature are well agreed with the variations of the weight loss and test temperature. The wear surface examinations and observations suggest that the dominant wear mechanism is an oxidational wear. The type and physical characteristics of the oxide layers produced on the surfaces contribute to the wear resistance as well as contribution of unique characteristics, such as high temperature, hardness and strength of Ni3Al + B. (C) 2004 Published by Elsevier B.V.
Keywords: boron-doped Ni3Al; intermetallic compound; adhesive wear; elevated temperatures